The Bloomsbury introduction to creative writing - Tara Mokhtari (Bloomsbury, 2016)
Covering a wide range of forms and genres, 'The Bloomsbury introduction to creative writing' is a complete introductory manual for students of creative writing. Through a structured series of practical writing exercises - perfect for the classroom, the writer's workshop or as a starting point for a portfolio of work - the book builds the student writer from the first explorations of their own voice, through to mastery of a wide range of genres and forms. 'The Bloomsbury introduction to creative writing' covers such genres as: autobiographical writing, short fiction, poetry, screenwriting, writing for performance, and writing for digital media. With practical guidance on writing scholarly critiques of your own work and a glossary of terms for ease of reference, this book is an essential manual for any introductory creative writing course and a practical companion for more advanced writers.